Knowledge and self-care adherence among type 2 diabetes mellitus patients with self-injecting insulin at klinik Pakar Perubatan (KPP), Hospital Universiti Sains Malaysia (HUSM) - Ying, Sze Ven (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Diabetes is one of the most common chronic diseases and of the top ten leading causes of death. Adequate glycemic control is vital in diabetes management to prevent complications secondary to uncontrolled diabetes. However, majority of diabetes patients were still not in satisfactorily controlled. Many type 2 diabetes mellitus (T2DM) patients delay or discontinue the use of insulin, even insulin use is required to achieve adequate glycaemic control. Complicating issues and lifestyle changes associated with self-injecting insulin diabetes patients make the issues of adherence to prescribed diabetes management plan more difficult than other illnesses. Level of diabetes knowledge had influences on the optimal diabetes care. Thus, ojectives of this study were to examine the knowledge and self-care adherence among T2DM patients with self-injecting insulin. A quantitative study had been carried out on 40 T2DM patients at HUSM, Kelantan, Malaysia. Validated Brief DKT with reliability Cronbach's alpha 0. 70 and SDSCA with reliability Cronbach's alpha for each of the regimen areas, (1) Diet: a=O. 70, (2) Exercise: a=O. 71, (3) SelfMonitoring Blood Glucose: a=0.89 and (4) Medication: a=1.00 was used to assess the knowledge and self-care adherence respectively in this study. Ethical clearance was obtained from the Ethical and Research Committe {Human) of USM. Duration of data collection was from January 2011 to February 2011. Data were analyzed via Chi-Square and One-Way Analysis of Variance {ANOVA) Test. Generally more than half of the respodents (52.5%) had poor level of overall diabetes knoweldge and general diabetes knowledge respectively and 62.5% had poor level of insulin knowledge. Sociodemographic factors were found significantly associated with overall diabetes knowledge; gender {p= 0.027), level of education {p=0.002), and income {p= 0.004), however there was no significant association between overall diabetes knowledge level with age {p= 0.269), ethnic (p= 0.342), marital status (p= 0.168), duration of diabetes (p= 0.920), duration of injected insulin (p= 0.979) and frequency of insulin injection in one day (p= 0.495). On the other hands, there was no significant association for all of the four self-care regimen areas (1) Diet (p= 0.063), (2) Exercise (p= 0.302), (3) Self-Monitoring Blood Glucose {p= 0.089) and (4) Medication (p= 0.097) with overall knowledge level were found in this study. However, different level of self-care adherence was observed between different levels of knowledge groups. Respondents who had poorer level of overall diabetes knowledge group had poorer mean of self-care adherence. Majority of the respondents had low adherence to exercise and self-monitoring blood glucose, moderate adherence to diet and good adherence to medication. In conclusion, the findings of this study will provides a guideline for health care providers to improve the diabetes knowledge and self-care practices among type 2 diabetes mellitus patients with self-injecting insulin.